2016
DOI: 10.3390/ani6020011
|View full text |Cite
|
Sign up to set email alerts
|

Dogs on the Move: Factors Impacting Animal Shelter and Rescue Organizations’ Decisions to Accept Dogs from Distant Locations

Abstract: Long-distance dog transfer programs are a topic of burgeoning interest in the animal welfare community, but little research has focused on such programs. This exploratory study, which surveyed 193 individuals associated with animal shelter and rescue organizations in the United States, evaluated factors that impacted organizations’ decisions to transfer in dogs over long distances (>100 miles) and assessed what criteria were commonly valued by destination organizations. Specifically, we examined the following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 15 publications
0
30
1
1
Order By: Relevance
“…A majority (73.1%) of the study dogs were transported via air. A published survey of shelters nationwide indicated that only 34% of relocated dogs were transported via air [7]. Though our multivariate analysis did not show a difference based on transport method in the odds of developing disease, the difference in our study population due to the frequency of air travel may limit generalizability of this sample to the broad population of dogs who are relocated nationally.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…A majority (73.1%) of the study dogs were transported via air. A published survey of shelters nationwide indicated that only 34% of relocated dogs were transported via air [7]. Though our multivariate analysis did not show a difference based on transport method in the odds of developing disease, the difference in our study population due to the frequency of air travel may limit generalizability of this sample to the broad population of dogs who are relocated nationally.…”
Section: Discussioncontrasting
confidence: 56%
“…Nonetheless, scientific data evaluating these best practices remain limited. Recent articles exploring transport decision-making [7] and infectious disease in transported felines [8] have begun efforts to objectively analyze non-disaster-related relocation efforts.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, more than 15% of dogs visiting dog parks in the Southeast, and 4 to 5.3% of those in the Midwest and Northeast, were infected with hookworm, a nding that is particularly concerning given the recent reports of multiple drug-resistant hookworms in pet dogs, including Greyhounds [33][34][35]. Although we do not know the resistance status, six of the 12 Greyhounds sampled from dog parks in the present study were positive for hookworm, and ve of those six were reported by the owner to be on a HWCM at the time they were sampled, compared to 57.7% of non-Greyhound, hookworm positive dogs that were reportedly receiving a HWCM (data not shown).…”
Section: Discussionmentioning
confidence: 69%
“…Only about 24% of animal shelters and rescue organizations perform fecal testing/deworming prior to transporting dogs to a new facility [5]. Over 114,000 dogs were transported into Colorado from out-ofstate, by more than 130 animal shelters and rescue groups, from 2014 to 2017.…”
Section: Discussionmentioning
confidence: 99%